ANALISIS PENGARUH DIVIDEN TERHADAP INDIKATOR KUALITAS LABA - Lita Fauziah; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2019)
This research aims to examine the relationship between dividend and earnings quality. This research examine four dividend features: dividend-paying status, dividend size, dividend changes, and dividend persistence. The samples consist of 72 firms from the manufacturing industry in the years 2014-2016. Multiple regression is used for testing hypotheses. The results show that dividend-paying status, dividend size, dividend increase, and persistence in dividend payment have significant positive association with earnings quality. Overall, the results show that dividend-paying status, dividend size, increase in dividend size, and persistence in dividend payment are indicators or signals of higher earnings quality. This study examines only the manufacturing firms listed on the Indonesia Stock Exchange.